The Effects of Mass Loss on The Evolution of BD+60Â°2522 - Aprilia Aprilia; Djoni N. Dawanas (Institut Teknologi Bandung, 2004)
BD+60°2522 (V = 8.7 mag) is the ionizing star of NGC 7635, the so-called Bubble Nebulae – wind-blown bubble created by the interaction of the stellar wind of BD+60°2522 with the ambient interstellar medium. It is classified as an O6.5 IIIef with mass loss rate M76.510−ô¾/year. The present mass of the star is 50 Mô¾. We carry out evolutionary calculations for the star with and without mass loss and we find that the initial mass of the star is 63 Mô¾ and its present age is years. The main sequence lifetime for BD+60°2522 is longer compared with that computed without mass loss; the difference is years. Comparing the mass and the age of NGC 7635 with BD+60°2522, we find that the bubble nebulae did not form since the ZAMS phase of the star.